About Carson v. Makin: Legal Contours of the Free Exercise of Religion in US Educational Settings (Forum, 2022)
This article reviews the case Carson v. Makin (2022) issued by the US Supreme Court, which analyzes the application of the First Amendment of the US Constitution in educational settings. After briefly reviewing the precedents which frame the decision, this article examines the arguments made by the majority and the dissenting votes relating to the Free Exercise Clause and the Establishment Clause; the constitutional leeway for states to favor one clause or the other, and the autonomy of religious organizations under the federal Constitution.
Keywords: Religious exercise; Education; First Amendment; Equality; Autonomy of religious organizations; Federalism